Synthesis of mesoporous silica coated gold nanorods loaded with methylene blue and its potentials in antibacterial applications - Fernández-Lodeiro, Adrián (2021)
POCI-01-0145-FEDER—007265 contract under DL57 SFRH/BD/52528/2014